Enhancement of mechanical behavior of resin matrices and fiber reinforced polymer composites by incorporation of multi-wall carbon nanotubes. (April 2021) - Su, Chang; Wang, Xin; Ding, Lining; Yu, Pancheng
Abstract: Herein, to enhance the toughness of resins and tensile strength of fiber-reinforced polymers (FRPs), multi-wall carbon nanotubes (MWCNTs) were incorporated as a toughening material into resin matrices. The effects of the MWCNT addition on the fracture toughness ( K IC ) and mechanical properties of epoxy and vinyl ester resins, and the tensile strength ( σ r ) and stiffness of impregnated basalt, carbon, and glass fiber rovings were systematically examined. The enhancement mechanism was studied by scanning electron microscopy (SEM). The enhancement in the tensile strength of the FRPs was predicted. The results showed that as compared to pure epoxy resin, the 0.3 wt% MWCNT-modified epoxy resin exhibited elevated K IC, tensile strength ( σ t ), flexural strength ( σ f ), and impact strength ( α cU ). Similar improvements were discovered for the MWCNT-modified vinyl ester resins. Concentrated tortuous textures due to the bonding and bridging effects of MWCNTs were observed on the fracture surface by SEM. The σ r of the basalt, carbon, and glass rovings obviously increased with the addition of MWCNTs, owing to the combined action of restricted crack propagation and the promoted co-stress of fibers. Additionally, the σ r of MWCNT-modified basalt and carbon rovings exhibited a lower dispersion, resulting in a higher guaranteed strength. The modification method proposed above can effectively improve the mechanical properties and design strength of FRP. Highlights: Due to the bridging effect of MWCNTs, leads to better mechanical properties of resin. Mechanism of mechanical properties enhancement is revealed by microscopy analysis. The tensile strength of impregnated fiber roving has been enhanced by adding MWCNTs. The design strength of MWCNT-modified FRP is increased by up to 17%. Models of the relationship between tensile strength of FRP and contents of MWCNT.